Methicillin- and Inducible Clindamycin-Resistant Staphylococcus aureus among Patients with Wound Infection Attending Arba Minch Hospital, South Ethiopia. (1st April 2019) - Mama, Mohammedaman; Aklilu, Addis; Misgna, Kassahun; Tadesse, Molla; Alemayehu, Eyerusalem
Abstract : Background . Wound infection is one of the most common hospital-acquired infections. Different bacteria cause infection, of which Staphylococcus aureus is one of the known bacteria in causing infection with increased drug-resistant isolates. Objective . To assess the prevalence and antimicrobial susceptibility pattern of methicillin and inducible clindamycin-resistant Staphylococcus aureus among patients with wound infections attending Arba Minch Hospital. Methods . A facility-based cross-sectional study was conducted from April to June 2017. A pretested questionnaire was used to collect demographic data and clinical characteristics. Wound swabs were cultured and identified by standard techniques. Antibiotic susceptibility tests were performed by the Kirby–Bauer disc diffusion method. Methicillin resistance was detected using the cefoxitin (30  μ g) antibiotic disc while inducible clindamycin resistance was detected by the D-zone test. The data were analyzed using Statistical Package for Social Science, version 20.p value <0.05 was considered statistically significant. Results . A total of 161 patients were enrolled and a majority of them were female (90, 50.9%). Among the collected samples, 79 (49.7%) were positive for S. aureus ; of this, methicillin resistance accounted for 65 (82.3%). Out of 22 (27.8%) erythromycin-resistant isolates, 19 (24.1%) showed inducible clindamycin resistance. Methicillin-resistant S. aureus showed higher resistance against tetracycline (72.3%) followed by cotrimoxazole (43.1%) and 100% sensitivity to vancomycin. The overall prevalence of inducible clindamycin resistance among methicillin-resistant isolates was 16 (24.6%). Conclusion . The increasing prevalence of methicillin-resistant S. aureus and the coresistance against other therapeutic options like clindamycin is becoming an obstacle in the treatment of infections which need attention from concerned bodies.